Phylogenetic placement, species delimitation, and cyanobiont identity of endangered aquatic Peltigera species (lichen‐forming Ascomycota, Lecanoromycetes)1. Issue 7 (1st July 2014) - Miadlikowska, Jolanta; Richardson, David; Magain, Nicolas; Ball, Bernard; Anderson, Frances; Cameron, Robert; Lendemer, James; Truong, Camille; Lutzoni, François
Abstract : Premise of this study: Aquatic cyanolichens from the genus Peltigera section Hydrothyriae are subject to anthropogenic threats and, therefore, are considered endangered. In this study we addressed the phylogenetic placement of section Hydrothyriae within Peltigera . We delimited species within the section and identified their symbiotic cyanobacteria. Methods: Species delimitation and population structure were explored using monophyly as a grouping criterion (RAxML) and Structurama based on three protein‐coding genes in combination with two nuclear ribosomal loci. The 16S and rbcLX sequences for the cyanobionts were analyzed in the broad phylogenetic context of free‐living and symbiotic cyanobacteria. Key results: We confirm with high confidence the placement of section Hydrothyriae within the monophyletic genus Peltigera ; however, its phylogenetic position within the genus remains unsettled. We recovered three distinct monophyletic groups corresponding to three species: P. hydrothyria, P. gowardii s.s., and P. aquatica Miadl. & Lendemer, the latter being formally introduced here. Each species was associated with an exclusive set of Nostoc haplotypes. Conclusions: The ITS region alone provides sufficient genetic information to distinguish the three morphologically cryptic species within section Hydrothyriae . Section Hydrothyriae seems to be associated with a monophyletic lineage of Nostoc, that has not been found in symbiotic association with other members of Peltigera . Capsosira lowei should be transferred to the genus Nostoc . Potential threats to P. aquatica should be re‐examined based on the recognition of two aquatic species in western North America.